2016
DOI: 10.1682/jrrd.2015.09.0172
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings of a novel measure of driving behaviors in Veterans with comorbid TBI and PTSD

Abstract: Abstract-Veterans of the military operations in Iraq andAfghanistan are at an elevated risk of driving-related accidents and fatalities compared with civilians. Combat exposure, military driving training, risk-seeking, traumatic brain injury (TBI), and posttraumatic stress disorder (PTSD) are all factors associated with driving-related risk. However, few empirical studies have observed driving patterns in this population, and the influence of these contributing factors remains unclear. This study utilized a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Also similar to Whipple et al, and in line with the findings of Hannold et al (2013), our focus group participants reported awareness of both their driving deficits and described their adoption of cognitive and behavioral strategies to facilitate appropriate driving. Similar to Zinzow et al (2013) and Whipple et al (2016), our Veteran participants reported experiencing environmental and social triggers while driving (e.g., unexpected items by the side of the road) that reminded them of deployment experiences, and which increased driving-related stress, anxiety, or anger. Driving difficulties such as increased driving stress, anxiety, and fatigue may make it challenging for Veterans to fully engage in daily activities or in community mobility to participate in their desired activities.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Also similar to Whipple et al, and in line with the findings of Hannold et al (2013), our focus group participants reported awareness of both their driving deficits and described their adoption of cognitive and behavioral strategies to facilitate appropriate driving. Similar to Zinzow et al (2013) and Whipple et al (2016), our Veteran participants reported experiencing environmental and social triggers while driving (e.g., unexpected items by the side of the road) that reminded them of deployment experiences, and which increased driving-related stress, anxiety, or anger. Driving difficulties such as increased driving stress, anxiety, and fatigue may make it challenging for Veterans to fully engage in daily activities or in community mobility to participate in their desired activities.…”
Section: Discussionmentioning
confidence: 61%
“…While driving on civilian roads, Veterans reported using similar tactics as those used during combat, such as battlemind training, straddling the middle of the road, not stopping at red lights, and making risky driving maneuvers (e.g., illegal U-turns). Whipple and colleagues (2016) studied driving behaviors in Veterans with comorbid TBI and PTSD, reporting that Veterans commonly experience frequent episodes of impatience, irritability, and frustration. Our participants demonstrated high-risk behaviors similar those described in the Whipple et al’s study, such as speeding, or accelerating through yellow lights.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of results should be made within the context of the study's strengths and limitations. These data, along with preliminary work by Whipple et al (2016), are among the first to examine the characteristics of a structured driving measure in a sample of former service members. The availability of a large clinical dataset and the incorporation of goldstandard, interview-based measures of PTSD are notable strengths of the project.…”
Section: Discussionmentioning
confidence: 99%
“…Established measures or scales derived from validated instruments are used in some research, although phenomena captured in these assessments generally target only a subset of problematic behavior (e.g., driving anger; Hwang et al, 2014;Strom et al, 2013). Whipple, Schultheis, and Robinson (2016)) begin to fill gaps in this literature with the introduction of the Veteran Driving Questionnaire (VDQ). Initial scale development examines situational anxiety, driving behaviors, and affective states in a small sample of well-adjusted veterans and veterans with comorbid brain injury and PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, PTSD or TBI are associated with an increased risk of aggressive driving in Veterans (Kuhn et al, 2010). Veterans with PTSD or TBI showed higher risky-driving behaviors and anxiety levels when driving under conditions, such as being “boxed in by other cars,” compared with nondisabled Veterans (Whipple et al, 2016). During deployment, Veterans are trained to execute battle-mind driving tactics, such as speeding, ignoring traffic rules, and driving in the middle of the road (Lew et al, 2010).…”
Section: Introductionmentioning
confidence: 99%